A New Approach to Identify the Methylation Sites in the Control Region of Mitochondrial DNA - Pérez-Muñoz, Ashael A.; de Lourdes Muñoz, María; García-Hernández, Normand; Santander-Lucio, Heriberto (Current Molecular Medicine, 2021)
Mitochondrial DNA (mtDNA) methylation has the potential to be used as a biomarker of human development or disease. However, mtDNA methylation procedures are costly and time-consuming. Therefore, we developed a new approach based on an RT-PCR assay for the base site identification of methylated cytosine in the control region of mtDNA through a simple, fast, specific, and low-cost strategy. Total DNA was purified, and methylation was determined by RT-PCR bisulfite sequencing. This procedure included the DNA purification, bisulfite treatment and RT-PCR amplification of the control region divided into three subregions with specific primers. Sequences obtained with and without the bisulfite treatment were compared to identify the methylated cytosine dinucleotides. Furthermore, the efficiency of C to U conversion of cytosines was assessed by including a negative control. Interestingly, mtDNA methylation was observed mainly within non-Cphosphate- G (non-CpG) dinucleotides and mostly in the regions containing regulatory elements, such as OH or CSBI, CSBII, and CSBIII. This new approach will promote the generation of new information regarding mtDNA methylation patterns in samples from patients with different pathologies or that are exposed to a toxic environment in diverse human populations.
Keywords: D-loop